QuantiFERON-TB reversion in children and adolescents with tuberculosis - Rodríguez-Molino, Paula; González Sánchez, Araceli; Noguera-Julián, Antoni; Soler-García, Aleix; Martínez Paz, Patricia; Méndez-Echevarría, Ana; Baquero-Artigao, Fernando; González Muñoz, Miguel; Ruíz-Serrano, María Jesús; Monsonís, Manuel; Sánchez León, Rocío; Saavedra-Lozano, Jesús; et al. (Frontiers in Immunology, 2024)
We analyzed 136 children with tuberculosis disease or infection and a positive QuantiFERON-TB (QFT) assay, followed-up for a median of 21 months (0.4-11years). QFT reversed in 16.9% of cases, with significant decreases in TB1 (-1.72 vs. -0.03 IU/ml, p=0.001) and TB2 (-1.65 vs. -0.43 IU/ml, p=0.005) levels compared to non-reverters. We found a higher QFT reversion rate among children under 5 years (25.0% vs 11.9%, p=0.042), and those with TST induration <15mm (29% vs 13.3%, p=0.055). Our data reveal that, although QFT test remained positive in the majority of children, reversion occurred in 16% of cases in a progressive and stable pattern. Younger age and reduced TST induration were associated with QFT reversion.